MR and CT Arthrography of the Wrist - Cerezal, Luis; de Dios Berná-Mestre, Juan; Canga, Ana; Llopis, Eva; Rolon, Alejandro; Martín-Oliva, Xavier; del Piñal, Francisco (Seminars in Musculoskeletal Radiology, 2012)
The study of the wrist represents a major diagnostic challenge because of its complex anatomy and the small size of individual structures. Recent advances in imaging techniques have increased our diagnostic capabilities. However, 3T magnets, multichannel specific wrist coils, and new MRI sequences have not restricted the indications of arthrographic imaging techniques (CT arthrography and MR arthrography). Distension of the different wrist compartments at CT arthrography and MR arthrography significantly improves the diagnostic accuracy for triangular fibrocartilage (TFC) complex injuries and carpal instability. Dedicated multichannel wrist coils are essential for an adequate study of the wrist, but the placement of these coils and the positioning of the wrist are also important for proper diagnosis. The development of dynamic multislice CT studies allows a diagnostic approach that combines dynamic information and the accurate assessment of ligaments and the TFC complex. New advances in arthroscopy have changed the anatomical description of the TFC with a functional division in the proximal and distal TFC complex, and they have allowed a better characterization of lesions of the TFC complex with subclassification of Palmer 1B and 1D lesions and description of new lesions not included in the Palmer classification, such as capsular injuries.
Keywords: triangular fibrocartilage; arthrography; MR arthrography; CT arthrography; wrist; ulnar impaction; carpal instability